Development of race of games teamwork (roger) learning model mediated by quizalize games for Pancasila education learning - Novita, Ima; Rochmadi, Nur Wahyu; Suhartono, H. Edi (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
This development research aims to produce a Race of Games Teamwork (ROGER) learning model mediated by quizalize games that is suitable for learning Pancasila Education. The development in this study uses the 4D Model procedure. The feasibility assessment of the learning model was carried out through a t-test on several syntax of the Race of Games Teamwork (ROGER) learning model mediated by quizalize games, namely the self-assessment stage obtained the results of t count 7.131 and t table was 1.699, the race stage obtained the result of t count of 9.394 and t table was 2.015, and the final stage of t calculation was 19,000 and t table was 6.313 based on these results, it can be concluded that the learning model The Race of Games Teamwork (ROGER) mediated by Quizalize Games is suitable for learning Pancasila Education.